Preoperative Botulinum Toxin and Progressive Pneumoperitoneum in Loss of Domain Hernias—Our First 100 Cases - Bueno-Lledó, José; Carreño-Saenz, Omar; Torregrosa-Gallud, Antonio; Pous-Serrano, Salvador (Frontiers in Surgery, 2020)
Abstract OBJECTIVES. Preoperative botulinum toxin type A (BT) and progressive pneumoperitoneum (PPP) are useful tools in the preparation of patients with loss of domain hernias (LODH). The purpose of our retrospective study is to report our experience in the treatment of 100 consecutive patients with LOHD, with the combined use of these techniques. METHODS Of the 753 patients operated on for ventral incisional hernia between June 2010 and December 2018 in our Hospital, 100 patients with LODH were analyzed retrospectively. Diameters of abdominal cavity and hernia sac, and volumes of incisional hernia (VIH) and abdominal cavity (VAC) were calculated from CT scan, based on the index of Tanaka. RESULTS The median insufflated volume of air for PPP was 8600 ± 4200 cc (4500–15250). BT administration time was 38.2 days (33-48). A significant average reduction of 15% of the VIH/VAC ratio was observed on CT scan after the combination of PPP and BT. CST and TAR were the most frequent repair techniques. Complete fascial closure was possible in 97% and mesh bridging was needed in three cases. In postoperative follow-up of 34.5 months (11-62), we reported 8 cases of hernia recurrence (8%). CONCLUSION PPP and BT are useful tools in the treatment of LOHD. These techniques significantly reduce the VIH/VAC ratio, allowing the reduction of the hernia content into the abdominal cavity, which represents a key factor in the management of these hernias.